Dearest Fríða: Arnfríður Sigurgeirsdóttir and Icelandic women’s migration to North America - Parsons, Katelin Marit (Milli Mála, 2025)
Many Icelandic women poets and writers migrated to North America in the late nineteenth and early twentieth centuries, some with larger family groups and others as single women who pursued independent careers, mainly as domestic workers and caregivers. However, few documents survive on women’s individual migration decisions or how and why they navigated the migration process. This article examines the poet Arnfríður Sigurgeirsdóttir (1880– 1954) and her correspondence with her aunt Petrína Guðmundsdóttir (1855–1928) in Canada. Petrína and her husband, Steingrímur Þorsteinsson, emigrated to North Dakota in 1893 with their sons Jón, Þorsteinn and Pétur. Petrína wrote several letters to her brother Sigurgeir, encouraging him to emigrate with Arnfríður. Petrína’s initially positive messages were followed by years of silence. Rather than describe her most difficult experiences as a migrant, she severed communication with her family in Iceland until her situation improved. After moving to Saskatchewan in 1905, Petrína began corresponding directly with her now-adult niece. Although Arnfríður was a talented and well-received poet, who published her poetry under the name Fríða, neither she nor Petrína had received a formal education. Arnfríður describes in her autobiography how she was treated as a social inferior in her home community as a child due to her father’s status. Petrína’s letters suggest that Arnfríður seriously considered emigrating to Canada immediately after the loss of her father in 1911. Her aunt offered to assist her in the migration process and to send the fare for the transatlantic crossing. Ultimately, Arnfríður decided to remain in Iceland after becoming romantically involved with her future husband, Þorlákur Jónsson. However, her family network connections remained a source of emotional support. The poet and her aunt continued to correspond until Petrína’s health declined, and their later letters served to reinforce their close emotional bond across the Atlantic Margar alþýðuskáldkonur og ...